Agronomic performance of striga resistant early-maturing maize varieties and inbred lines in the savannas of West and Central Africa - Badu-Apraku, Baffour; Lum, A.F. (Wiley, 2007)
The potential maize (Zea mays L.) yield in the savannas of West and Central Africa (WCA) is constrained by Striga hermonthica (Del.) Benth. parasitism. Field trials at Ferkessedougou, Côte d'Ivoire; Abuja, Nigeria; and Mokwa, Nigeria, in 2002, and at Mokwa and Abuja in 2004, evaluated the performance of 11 early maturing maize varieties under artificial Striga infestation and Striga-free conditions. Another trial at Mokwa and Abuja in 2004 evaluated 100 early maturing inbred lines under Striga infestation and Striga-free conditions. The varieties differed significantly in grain yield under both conditions. Acr 94 TZE Comp 5-W, Acr TZE Comp 5-Y, and TZE-W Pop × 1368 STR C1 were identified as promising varieties, based on grain yield, Striga damage ratings, and Striga emergence counts. The most promising variety, Acr 94 TZE Comp. 5-W in terms of high grain yield, reduced Striga damage and low Striga emergence, outyielded the reference entry by 2% under Striga-free conditions and 45% under Striga infestation. Ward cluster analysis of the varieties and inbred lines produced four major clusters each, under both Striga-infested and Striga-free conditions. In each case, the varieties and inbred lines assigned to each cluster under Striga infestation differed from those in the Striga-free conditions. Several inbred lines with high grain yield, low Striga emergence and reduced Striga damage were identified as sources of Striga resistance for maize breeding programs in WCA.